Dermoscopy findings of plantar vascular lesions. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
In the palmar and plantar region some lesions are distributed in a linear way, parallel to the dermatoglyphics. This pattern is characteristic of melanocytic nevus (2), mainly of those ones superficial. However, also the pustules of hand-foot-mouth disease, which are elsewhere roundish, in the palmar and plantar region are spindle-shaped. Also lesions with blood component, for instance ecchymoses and hemangioma as in our two cases can show a similar distribution. From a dermoscopy point of view, the melanic pigment is usually distributed along the furrows in melanocytic nevi, along the cristae in melanoma (1). Less known is the distribution of blood pigment, that in our cases was distributed along the furrows in the hemangioma, but in the space between the furrows in the ecchymosis.